Comparative phenotypic and genotypic discrimination of methicillin resistant and susceptible Staphylococcus aureus in Egypt - Abd El-Hamid, Marwa I; Bendary, M M (Cellular and Molecular Biology, 2015)
The present study was designed to elucidate the phenotypic and genotypic characterization of S. aureus isolates in Egypt. The antibiotic susceptibility pattern of 133 identified S. aureus isolates revealed that over 70% of the isolates were multi-drug resistant (MDR). Fifty MDR isolates were characterized using antibiotyping and different molecular typing methods. Amplification of mecA gene confirmed 30 strains as methicillin-resistant S. aureus (MRSA) and 20 as methicillin-sensitive S. aureus (MSSA). Generally, 22 MRSA (73.33%) and ten MSSA (50%) harbored Panton-Valentine leukocidin (pvl) gene with no statistically significant difference (p=0.093). Staphylococcal cassette chromosome (SCC) mec typing revealed that 48% of the typeable MRSA isolates possessed SCCmec type IV. SCCmec and antimicrobial susceptibility typing signified the presence of community-acquired (CA)-MRSA in Egypt. Surprisingly, all isolates of SCCmec types I, II and III and 50% of both MRSA isolates of SCCmec types IV and V possessed pvl gene. It was clear that staphylococcal protein A (spa) and coagulase (coa) typing discriminated the isolates into eight different groups, whilst polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) of coagulase gene yielded ten distinct RFLP banding patterns. This study presented the first baseline information on the characterization of MRSA and MSSA in Egypt.